Overcoming familiarity illusions in a single case with persistent déjà vu. Issue 7 (9th August 2021) - Ernst, Alexandra; Delrue, Gaël; Willems, Sylvie
ABSTRACT: While occasional déjà vu is benign in the general population, rare neuropsychological cases with persistent déjà vu have been described in the literature. We report the case of MN, a 25-year-old woman, who suffered a cerebral haemorrhage in the right thalamo-callosal region and experienced recurrent déjà vu episodes. Through clinical interviews and memory tasks related to déjà vu, we assumed that source memory errors and an inappropriate feeling of familiarity (measured by the number of false recognitions) were critically involved in MN's déjà vu. Based on this, we developed the first neuropsychological intervention dedicated to déjà vu. The rationale was to train MN to detect elements that could produce an inappropriate feeling of familiarity and to promote metacognitive awareness about déjà vu. This intervention was effective at reducing the frequency of déjà vu episodes in MN's daily life, as well as the number of false recognitions in memory tasks. In addition to its clinical contribution, this single-case study contributes to the limited literature on patients whose déjà vu is not related to epileptic abnormalities and medial temporal brain damage, and provide supportive evidence of the role of an erroneous feeling of familiarity and of metacognitive processes in déjà vu.